2012
DOI: 10.3892/etm.2012.780
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status deteriorates as the severity of diabetic foot ulcers increases and independently associates with prognosis

Abstract: The prognosis for diabetic foot ulcers (DFUs) remains poor. Nutritional status has not been identified as one of the factors affecting the outcome of DFUs. Therefore, indicators correlated with nutritional status and outcome were analyzed to investigate their relationship. A total of 192 hospitalized patients with Wagner grade 1–5 ulcers and 60 patients with Wagner grade 0 ulcers (all had type 2 diabetes) were assessed by the following: subjective global assessment (SGA), anthropometric measurements, biochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 30 publications
2
51
2
1
Order By: Relevance
“…To date, few studies have focused on the relationship between diabetic complications and malnutrition. In univariate analysis, studies have shown that diabetes patients with macrovascular complications or diabetic feet have a higher prevalence of malnutrition . Furthermore, Alejandro's study showed the presence of diabetic complications to be independently associated with malnutrition in multivariate analysis .…”
Section: Discussionmentioning
confidence: 99%
“…To date, few studies have focused on the relationship between diabetic complications and malnutrition. In univariate analysis, studies have shown that diabetes patients with macrovascular complications or diabetic feet have a higher prevalence of malnutrition . Furthermore, Alejandro's study showed the presence of diabetic complications to be independently associated with malnutrition in multivariate analysis .…”
Section: Discussionmentioning
confidence: 99%
“…24 DFU is a source of major suffering and financial costs for the patient, and also places a considerable burden on the patient's family, health-care professionals and facilities, and society, and malnutrition in general. 25,26 Diabetic foot ulcer severity is a more significant factor of subsequent mortality than coronary artery disease, peripheral arterial disease or stroke. 18 80% of non-traumatic limb amputations are attributable to diabetes, of which 85% are due to DFU.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, the predictive value of GNRI for prognosis has also been demonstrated for older age, dialysis patients, and cardiovascular patients [1013]. The Mini-Nutritional Assessment (MNA) is a well-validated nutritional screening tool with high sensitivity and specificity and is widely used in clinical practice to measure nutritional status [23].…”
Section: Discussionmentioning
confidence: 99%
“…Malnutrition is common in patients with limb-threatening DFU and has a significant influence on prognosis [10], including delayed wound healing [28], longer hospital stay, and increased mortality [7, 8, 29]. Moreover, as nutritional status is related to immunity, patients with poor nutritional status more commonly suffer from infection [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation